Empirical Study on Research Trends and Challenges in Cyber Security and Governance (International Journal of Food and Nutritional Sciences, 2023)
The buzz word "cyber security" covers the entire facts of protecting a company's resources, workforce, and maneuvers from online or web related hazards. A diversity of computer-generated protection resolutions are needed to diminish industry virtual hazard as virtual attacks become more recurrent and complicated and community networks become additional problematical. The availability, integrity and confidentiality of data are characteristically the focal point of cyber safety measures. Business services includes user authentication, accountability, reliability and authorization are maintained by these kinds of elements. The comprehensive cyber security strategy called cyber security authorities integrates with secretarial maneuvers and guards adjacent to the interruption of operations conveyed on by virtual threats or attacks. Cyber security governance characteristics include: frameworks for accountability, hierarchies for making decisions. The information technology sector should obtain the following six steps to help their own organization’s grow and sharpen their cyber security governance contents. Establish the current state; Create, review and update all cyber security standards, policies and progression; Approach cyber security from an enterprise lens; Increase cyber security awareness and training related activities to users; Cyber-risk analytics: How are different kinds of threats designed and risks contextualized and evaluated? And finally Monitor, measure, analyze, report and improve. The development and maintenance of cyber security capabilities that guarantee the secure use of digital services falls squarely on the shoulders of governments and businesses. This current trends and challenges related to the cyber security and its governance related activities are discussed in this empirical study.